The last days according to Jesus - Sproul, R. C. (Robert Charles), 1939-2017. (Grand Rapids, MI, Baker Book House, 1998)
As the new millennium approaches, theologian R.C. Sproul focuses on what Jesus himself taught about the last days and the timing of his return, in the author's first book-length treatment of this doctrine. 92 pp.
What did Jesus teach on Mount Olivet? -- What "generation" will witness the end? -- What "age" was about to end? -- What did Paul teach in his letters? -- What about the destruction of Jerusalem? -- What did John teach in Revelation? -- When is the resurrection? -- Who is the Antichrist? -- When is the Millennium?
Includes bibliographical references (pages 239-245) and indexes.
Keywords: Jesus Christ -- Prophecies; Bible. -- Prophecies -- Second Advent; Second Advent -- Biblical teaching